Relationship Between Leadership and Commitment with Quality Performance on U-Th-REE Processing Pilot Plant Construction in BATAN - Madyaningarum, Nunik; Berawi, Mohammed Ali; Miraj, Perdana (EKSPLORIUM, 2018)
Management area of leadership and commitment in the quality management system is a mean to achieve successful functions, even more on construction industry. The objective of this research is to analyze the correlation between leadership and commitment focus management area and quality performance as indicated by rework. Research location is uranium (U), thorium (Th), and rare earth elements (REE) processing pilot plant construction area in Center for Nuclear Minerals Technology-BATAN. Primary data were collected from the 36 of 37 submitted questionnaires, and representing 97 % response rate. The research used descriptive analysis, which depends on the poll and the use of Statistical Package for the Social Sciences (SPSS) main program for data analysis. The relationship between leadership and commitment and quality performance was analyzed using spearman rank correlation coefficient. Findings of research provide guideline and alert to project managers or management of organization where leadership, commitment, infrastructure, and environmental work have moderate to strong correlation to rework level. The results further revealed that there is no relationship between responsibility and authority for the management system and organizational policy and construction quality performance. The research provides evidence, in fact to achieve the quality performance of a pilot plant construction must be concerned with leadership attribute, maintaining commitment and provide support resources on the whole project cycle.